Analisis Minat Belajar Siswa pada Pembelajaran Matematika Menggunakan Media Pembelajaran Video Animasi - Firda Rahmawati; Attin Warmi (Journal on Education, 2023)
This study was conducted to describe the students' interest in learning mathematics using animated video-based learning media. The subjects of this study were the IV grade students at SDN Kalibaru 5 as many as 35 students. The study method used is descriptive method and used a qualitative approach. The instrument used is a non-test instrument by a questionnaire. The data collection technique was carried out by distributing a questionnaire that containing 10 statements. The results showed that students' interest in learning mathematics when using animated video-based learning media was in the very good category, this was seen in the percentage of each indicator which was dominated between 76%-100%.